How much urban air quality is affected by local emissions: A unique case study from a megacity in the Pearl River Delta, China. (15th April 2023) - Tang, Meng-Xue; Huang, Xiao-Feng; Yao, Pei-Ting; Wang, Run-Hua; Li, Zhi-Jie; Liang, Chao-Xi; Peng, Xing; Cao, Li-Ming; Du, Ke; Yu, Kuangyou; Guo, Song
Abstract: In March 2022, the resurgence of COVID-19 cases in Shenzhen, a megacity in the Pearl River Delta (PRD) region of China, led to unusual restrictions on anthropogenic activities within a single city, in contrast to the restrictions COVID-19 caused on a national scale at the beginning of 2020. In this unique event, we found that only under unfavorable meteorological conditions did substantial urban local emission reductions have an impact on air pollutant changes (−42.4%–6.6%), whereas the deweathered changes were very small (−8.3%–3.4%) under favorable meteorological conditions. Primary anthropogenic pollutants, such as NO2, toluene, BC, and primary organic aerosol (POA), responded most considerably to emission reductions from early morning to noon during unfavorable meteorological days; for secondary organic aerosol (SOA), regulating the daytime total oxidant (O x  = O3  + NO2 ) was found to be more effective than controlling its precursors within the city scale, whereas secondary nitrate displayed the opposite trend. Since O x changed little during the urban lockdown despite the remarkable decrease in precursors, it is emphasized that regionally coordinated control of VOCs and NO x is necessary to effectively reduce O x levels. In addition, Shenzhen's NO x emission reduction efforts should be sustained in order to control PM2.5 and O3 pollution synergistically for long-term attainment. Graphical abstract: Image 1 Highlights: Reductions in urban emissions had a remarkable impact only under unfavorable meteorology. Primary pollutants responded to the urban lockdown considerably from morning to midday. Reducing O x at the regional scale is required to effectively mitigate urban SOA. Continuous effort on NO x emission control is suggested for Shenzhen in the future.